1981
DOI: 10.1177/00220345810600051101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contact Stress, Sliding Velocity, and Surface Roughness on the Sliding Wear of a Composite Restorative

Abstract: The influence of several experimental parameters on the sliding-wear behavior of a composite restorative has been examined. The results demonstrate that: 1) Changes in surface finish and sliding velocity have little effect on the moderate wear-rate observed at nominal levels of stress, and 2) increased contact stress can profoundly alter wear mechanisms and produce marked surface failure at levels well within the range associated with human mastication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…According to the recent results of Composite A of Bailey et al, 10 increasing the stress from 10 to 15 MPa on enamel pins produces severe damage accompanied by catastrophic wear. In going from the low to high stresses above, the wear rates increased by something like a factor of 2000.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the recent results of Composite A of Bailey et al, 10 increasing the stress from 10 to 15 MPa on enamel pins produces severe damage accompanied by catastrophic wear. In going from the low to high stresses above, the wear rates increased by something like a factor of 2000.…”
Section: Discussionmentioning
confidence: 98%
“…-All specimens were prepared from the commercial dental composite restorative designated here as Composite A,*t which consists of a BIS-GMA-based resin with a quartz reinforcing filler. The restorative was Received for publication August 18,1981 Accepted for publication December 10,1981 This work was supported by Interagency Agreement No. YO1-DE-40015 from the National Institute of Dental Research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…focussing either on attrition or abrasion. Two-body tests for restorative materials either use human enamel [26] or a hard material, such as alumina [27] or steatite [28], as the abrader. For three-body tests, an abrasive medium, such as toothpaste slurry [29,30], or an abrasive food, such as rice or millet seeds [31,32], is typically used.…”
Section: Laboratory (In Vitro) Test Methodsmentioning
confidence: 99%
“…[6][7][8] In the present work, the wear characteristics of a polymeric composite* in sliding contact with a stylus fashioned from human enamel were evaluated as a function of the stiffness of the stylus-restorative contact. Recent investigations9 have shown that the stiffness parameter is important in structural vibration, machining, and other mechanical processes which contribute to wear.…”
Section: Introductionmentioning
confidence: 99%